Microlearning Content for Digital Zakat Education: Bite-Sized Learning Strategies for the Smartphone Generation - Haryanti, Peni (Corolla International Conference, 2025)
This study aims to explore the effectiveness of microlearning content design in improving digital zakat literacy among the smartphone generation. The background to this research stems from the gap between the national zakat potential of Rp 327 trillion and the current realization around12.5%, partly due to the low public understanding and accessibility of the digital zakat system. Given the characteristics of Generation Z, who tend to prefer short, interactive content that is easily accessible via mobile devices, microlearning is considered an appropriate learning strategy. The study used a mixed methods approach with explanatory sequential design and a Design-Based Research (DBR) framework to develop and test a prototype of microlearning-based zakat education content. Data analysis was conducted using SEM-PLS with 300 quantitative respondents and in-depth interviews with 30 qualitative respondents. The results showed that microlearning design significantly influenced digital zakat literacy (β = 0.612), user engagement (β = 0.348), and behavioral intention (β = 0.187). User engagement served as an important mediator in strengthening the relationship between digital zakat literacy and online zakat payment intention. The tested structural model was able to explain 60.3% of the variance in behavioral intention and 40.2% of the variance in actual digital zakat usage. These findings confirmed that interactive microlearning strategies, such as gamification and personalized content, can increase digital zakat adoption. This study provides theoretical contributions by integrating cognitive load theory, dual-coding theory, and Islamic pedagogy into the context of digital zakat literacy, and provides practical implications for zakat institutions and educational technology developers in designing more effective educational content.